2021
DOI: 10.1186/s13613-021-00924-3
|View full text |Cite
|
Sign up to set email alerts
|

Admission serum myoglobin and the development of acute kidney injury after major trauma

Abstract: Background Myoglobin and creatine kinase (CK) are both established markers of muscle injury but their hospital admission values have never been compared to predict post-traumatic acute kidney injury (AKI). Methods An observational registry study of consecutive trauma patients admitted to a major regional trauma centre. The primary outcome was stage 1 or more AKI in the first 7 days after trauma. We assessed the association of hospital admission myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
(56 reference statements)
2
14
0
Order By: Relevance
“…www.anesthesia-analgesia.org 845 years old, and almost 75% of the patients were male. Patients were severely injured, with a median ISS of 26 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). RM was highly prevalent in the global cohort (58.1%), and 55 (23.2%) patients presented with intense RM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…www.anesthesia-analgesia.org 845 years old, and almost 75% of the patients were male. Patients were severely injured, with a median ISS of 26 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). RM was highly prevalent in the global cohort (58.1%), and 55 (23.2%) patients presented with intense RM.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, several studies have reported a prevalence of intense traumatic RM (CK >5000 U/L) at 13% to 31%, which is consistent with our results. 32–36…”
Section: Discussionmentioning
confidence: 99%
“…76,78,79 Serum CK levels rise within 12 h of injury and peak in 24−72 h, which makes it more useful than myoglobin for diagnosing rhabdomyolysis, 71,80 but there are still conflicting data on whether CK levels correlate with progression to renal failure and clear cutoffs have not been established prospectively. 75,[81][82][83] Similarly, the evidence regarding serum myoglobin levels for prognostication in rhabdomyolysis is also mixed. 78,82,84 Regardless, once the diagnosis of rhabdomyolysis has been made, the most important next steps include identifying high-risk features and proactively treating the physiologic and metabolic disturbances associated with this syndrome.…”
Section: Electrolyte Abnormalities In Traumatic Rhabdomyolysismentioning
confidence: 99%
“…75,[81][82][83] Similarly, the evidence regarding serum myoglobin levels for prognostication in rhabdomyolysis is also mixed. 78,82,84 Regardless, once the diagnosis of rhabdomyolysis has been made, the most important next steps include identifying high-risk features and proactively treating the physiologic and metabolic disturbances associated with this syndrome. An in-depth review of the treatment of rhabdomyolysis is outside of the scope of this article but several recent publications are available for the reader for review.…”
Section: Electrolyte Abnormalities In Traumatic Rhabdomyolysismentioning
confidence: 99%
See 1 more Smart Citation